Der Doge vor dem Altar –: Gottesdienste als Thema politischer Visualisierung in der zweiten Hälfte des 16. Jahrhunderts in Venedig - Schilling, Ruth (Comparativ, 2008)
The visual representation of rulers kneeling in front of an altar can reveal how and to which extent the combination of religion and politics is part of each individual political culture. In Venice, a special type of representing the doge participating in a religious service was generated in the second half of the 16th century. At first one might argue that this demonstrates how the combination of religious and political rights was visualized by using specifically post-tridentine catholic symbols. However, a detailed analysis shows the priority of the ducal dignity over confessional symbols.